A new method to correct for host star variability in multiepoch observations of exoplanet transmission spectra. Issue 4 (13th July 2022) - Panwar, Vatsal; Désert, Jean-Michel; Todorov, Kamen O; Bean, Jacob L; Stevenson, Kevin B; Huitson, C M; Fortney, Jonathan J; Bergmann, Marcel
ABSTRACT: Transmission spectra of exoplanets orbiting active stars suffer from wavelength-dependent effects due to stellar photospheric heterogeneity. WASP-19b, an ultra-hot Jupiter ( T eq ∼ 2100 K), is one such strongly irradiated gas-giant orbiting an active solar-type star. We present optical (520–900 nm) transmission spectra of WASP-19b obtained across eight epochs, using the Gemini Multi-Object Spectrograph (GMOS) on the Gemini-South telescope. We apply our recently developed Gaussian Processes regression based method to model the transit light-curve systematics and extract the transmission spectrum at each epoch. We find that WASP-19b's transmission spectrum is affected by stellar variability at individual epochs. We report an observed anticorrelation between the relative slopes and offsets of the spectra across all epochs. This anticorrelation is consistent with the predictions from the forward transmission models, which account for the effect of unocculted stellar spots and faculae measured previously for WASP-19. We introduce a new method to correct for this stellar variability effect at each epoch by using the observed correlation between the transmission spectral slopes and offsets. We compare our stellar variability corrected GMOS transmission spectrum with previous contradicting MOS measurements for WASP-19b and attempt to reconcile them. We also measure the amplitude and timescale of broad-band stellar variability of WASP-19 from TESS photometry, which we find to be consistent with the effect observed in GMOS spectroscopy and ground-based broad-band photometric long-term monitoring. Our results ultimately caution against combining multiepoch optical transmission spectra of exoplanets orbiting active stars before correcting each epoch for stellar variability.